2006
DOI: 10.1177/1534484306290106
|View full text |Cite
|
Sign up to set email alerts
|

Expatriate Preparation: A Critical Analysis of 25 Years of Cross-Cultural Training Research

Abstract: Although much research in the 1960s and 1970s was devoted to crosscultural issues such as expatriate employment, researchers moved away from doing cross-cultural research in order to direct their efforts toward the hot topics of the time. However, the past few decades have seen an exponential increase in the globalization of our economy, and this ever-increasing globalization has made the need for cross-cultural research salient once again. In the past decade alone, there has been an explosion of research exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
198
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 211 publications
(198 citation statements)
references
References 44 publications
(232 reference statements)
0
198
0
Order By: Relevance
“…For example Lievens et al (2003) mention that some previous scholars showed that cross-cultural training contributes to expatriate adjustment and performance. However, other scholars found the results to be inconclusive (Littrell et al 2006). To that end, there is no single answer to the relationship between the effectiveness of cross-cultural training and expatriate adjustment and performance.…”
Section: Cross-cultural Trainingmentioning
confidence: 98%
“…For example Lievens et al (2003) mention that some previous scholars showed that cross-cultural training contributes to expatriate adjustment and performance. However, other scholars found the results to be inconclusive (Littrell et al 2006). To that end, there is no single answer to the relationship between the effectiveness of cross-cultural training and expatriate adjustment and performance.…”
Section: Cross-cultural Trainingmentioning
confidence: 98%
“…33,34 CCT is traditionally designed for preparing international trainees by targeting cultural issues. 33 CCT aims to develop the skills and knowledge needed to interact appropriately and effectively with host-country nationals (HCNs) 34,35 and with members of multicultural teams. 35 Researchers have identified three goals for CCT.…”
Section: The Role Of Cross-cultural Trainingmentioning
confidence: 99%
“…33 CCT aims to develop the skills and knowledge needed to interact appropriately and effectively with host-country nationals (HCNs) 34,35 and with members of multicultural teams. 35 Researchers have identified three goals for CCT. The first is to assist expatriates in determining acceptable cultural behaviors and appropriate ways to complete tasks in a new environment.…”
Section: The Role Of Cross-cultural Trainingmentioning
confidence: 99%
See 2 more Smart Citations